2017
DOI: 10.1016/j.envexpbot.2017.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Bigger is not always better: Reducing leaf area helps stay-green sorghum use soil water more slowly

Abstract: A B S T R A C TStay-green, a trait that confers delayed leaf senescence and improved grain yield under post-anthesis drought, has been associated with smaller canopies at flowering and increased water uptake during the post-flowering period. It has been shown that the main stay-green quantitative trait loci reduce leaf area via reduced tiller number and smaller leaves. To show that these canopy characteristics are directly linked to water savings, we grew near-isogenic lines with and without stay-green introgr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 32 publications
0
32
0
Order By: Relevance
“…Delayed senescence under water deficit can be engineered via the metabolism of cytokinins (110), but in field conditions it often appears as a consequence of early events in the plant cycle ( Table 1). In sorghum, the stay-green phenotype is probably the consequence of low water consumption during the vegetative phase in plants presenting reduced tillering and lower leaf size (53). Low water consumption increases water availability during late stages of the plant cycle, thereby causing the stay-green phenotype (53) ( Table 1).…”
Section: Genomic Selectionmentioning
confidence: 99%
“…Delayed senescence under water deficit can be engineered via the metabolism of cytokinins (110), but in field conditions it often appears as a consequence of early events in the plant cycle ( Table 1). In sorghum, the stay-green phenotype is probably the consequence of low water consumption during the vegetative phase in plants presenting reduced tillering and lower leaf size (53). Low water consumption increases water availability during late stages of the plant cycle, thereby causing the stay-green phenotype (53) ( Table 1).…”
Section: Genomic Selectionmentioning
confidence: 99%
“…However, this was not observed in this study ( Figure 2). This contrast may be because the stay-green trait can improve yield under drought conditions by reducing plant size at anthesis through a number of mechanisms other than reducing tillering, including reducing leaf number of the main stem, increasing sizes of upper leaves of the main stem [12,13], or accelerating age-related senescence of lower leaves [34].…”
Section: The Impacts Of Dtf and Ftn On Grain Yield Varied Across Envimentioning
confidence: 99%
“…Hence, the approach of leaf senescence is a final measure taken by plants to cope with severe water stress and can result in severe yield declines under drought. However, it has also been found that stay-green lines show increased senescence of older leaves lower in the canopy even under water non-limited conditions which reduces plant transpiration and leads to pre-anthesis water savings (George-Jaeggli et al, 2017).…”
Section: Increasing Te By Manipulation Of Transpiration Ratesmentioning
confidence: 99%
“…Ultimately, this leads to a smaller canopy that reduces pre-anthesis transpiration and conserves soil water that can be used during grain filling (George-Jaeggli et al, 2017; van Oosterom et al, 2011). This has been found to be beneficial for improved yield under post-anthesis water limitation, as reported by Borrell et al…”
Section: Increasing Te By Manipulation Of Transpiration Ratesmentioning
confidence: 99%
See 1 more Smart Citation